#### Answer

$(x-3)^2+(y+1)^2=9$

#### Work Step by Step

RECALL:
The standard form of the equation of a circle with a center at $(h, k)$ and a radius of $r$ units is:
$(x-h)^2+(y-k)^2=r^2$
The given circle has its center at $(3, -1)$.
The point on the circle that is directly to the left of the center is $(0, -1)$.
This point is 3 units away from the center.
This means that the radius is 3 units.
Since the center is at (3, -1), we know that h=3 and k = -1.
The radius is 3 units so r = 3.
Therefore, the equation of the given circle is:
$(x-3)^2 + [(y-(-1)]^2=3^2
\\(x-3)^2+(y+1)^2=9$